The Clinical Features and Diagnosis of Canavan’s Disease: A Case Series of Iranian Patients - KARIMZADEH, Parvaneh (Iran J Child Neurol, 2014)
OBJECTIVE: Canavan’s disease is a lethal illness caused by a single gene mutation that is inherited as an autosomal recessive pattern. It has many different clinical features especially in the non-Ashkenazi Jewish population. MATERIAL & METHODS: 45 patients were referred to the Pediatric Neurology Department of Mofid Children’s Hospital in Tehran-Iran from 2010–2014 with a chief complaint of neuro developmental delays, seizures, and neuroimaging findings of leukodystrophy were included in this study. Magnetic Resonance Spectrometry (MRS) and neuro metabolic assessment from a referral laboratory in Germany confirmed that 17 patients had Canavan’s disease. RESULTS: Visual impairment, seizure, hypotonia, neuro developmental arrest, and macrocephaly were the most consistent findings in the patients in this study. Assessments of neuro developmental status revealed that 13 (76%) patients had neuro developmental delays and 4 (24%) patients had normal neuro development until 18 months of age and then their neuro developmental milestones regressed. In this study, 100% of cases had macrocephalia and 76% of these patients had visual impairment. A history of seizures was positive in 8 (47%) patients and began around 3 months of age with the most common type of seizure was tonic spasm. EEGs were abnormal in all epileptic patients. In ten of the infantile group, we did not detect elevated level of N-acetylaspartic acid (NAA) in serum and urine. However, the MRS showed typical findings for Canavan’s disease (peaks of N-acetylaspartic acid). CONCLUSION: We suggest using MRS to detect N-acetylaspartic acid as an acceptable method for the diagnosis of Canavan’s disease in infants even with normal serum and urine N-acetylaspartic acid levels.